(untitled) (Fiep Bulletin - online, 2011)
This study is referenced classes teaching practice component Curriculum for Physical Education which are applied in an Institution of Higher Education in Sao Paulo. From CNE Resolutions 01 and 02, 2002, which established the Curriculum Guidelines for Undergraduate Programs, there was a reorganization of the curriculum of courses in Physical Education. One of the main changes is the possibility of 400 hours of teaching practice as a curricular component along the course, which made it possible to distribute the different disciplines of the course to practice teaching. The aim of this study is to establish the benefits of teaching practice as a curricular component of the course subjects and the perception of approximation theory and practice of future teachers. The methodology was a descriptive, and the instrument was a questionnaire. The data showed that 98% of respondents reported that visits schools allow the questioning of the theories presented in class, and believe that the lessons of teaching practice contributed to the training. It was concluded that vocational training was more linked to professional practice, allowing the student teacher a teaching practice more responsible.